PEMBUATAN GENTENG BERSERAT TANDAN KOSONG KELAPA SAWIT - Tarkono Tarkono; Nandang Nandang (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2018)
The utilization of oil empty bunches palm (EFBP) is limited, while the supply of EFBP is abundant. The most utilization of EFBP is in agriculture, while EFBP fibers have the opportunity to be developed in the field of engineering, for example as a composite material reinforcement material. In the construction field, EFBP fibers can contribute as a mixture of substances for cement tile products. The purpose of adding fiber is to distribute the stress on fibrous cement roof tiles. With evenly distributed stress, the strength of the tile will be higher. The production process of EFBP fibrous cement board is carried out without combustion, with materials in the form of portland cement, marble powder, CaCo3 powder and EFBP fiber and water. Based on the mechanical test that the fibrous EFBP tile can still be applied as a roof, this is evidenced by the majority of its mechanical properties meeting SNI standards. However, fibrous EFBP roof tiles have a flame spread value of 61.5 which means that they still need to be repaired so that the tile is not flammable. Thus, EFBP fibers can be used as an alternative fiber cement tile in order to improve product quality.Keywords: cement tile , fibre, EFBP